Turbulent flow structure around a single submerged angled spur dike under ice cover - Li Guowei; Sui Jueyi; Sediqi Sanaz (Journal of Hydrology and Hydromechanics)
This experimental study examines the velocity fields around the single submerged spur dike in a large-scale flume under three flow conditions: open channel, smooth ice-covered, and rough ice-covered. The effects of dike orientation were investigated for alignment angles of 90°, 120°, and 135°. Instantaneous three-dimensional velocity components were recorded using an acoustic Doppler velocimeter. Results show that the spur dikes generate distinct transverse flow regions in the streamwise, lateral, and vertical directions. Alignment angles greater than 90° reduced streamwise velocity near the dikes, while the frontal surface of the dike tip exhibited increased velocity magnitudes. Downstream, significant variations in Reynolds shear stress were observed, driven by flow separation and the formation of a recirculation wake zone. Quadrant analysis revealed that under ice-covered conditions, turbulent interactions near the dike tip were dominated by ejection and sweep events, whereas sweep events were more prevalent in open channel flows, influencing overall flow dynamics.